Association of the Long Non-coding RNA Steroid Receptor RNA Activator (SRA) with TrxG and PRC2 Complexes. - Patompon Wongtrakoongate; Gregory Riddick; Suthat Fucharoen; Gary Felsenfeld (PLoS Genetics)
Long non-coding RNAs (lncRNAs) have been recognized as key players in transcriptional regulation. We show that the lncRNA steroid receptor RNA activator (SRA) participates in regulation through complex formation with trithorax group (TrxG) and polycomb repressive complex 2 (PRC2) complexes. Binding of the SRA-associated RNA helicase p68 preferentially stabilizes complex formation between SRA and a TrxG complex but not PRC2. In human pluripotent stem cells NTERA2, SRA binding sites that are also occupied by p68 are significantly enriched for H3K4 trimethylation. Consistent with its ability to interact with TrxG and PRC2 complexes, some SRA binding sites in human pluripotent stem cells overlap with bivalent domains. CTCF sites associated with SRA appear also to be enriched for bivalent modifications. We identify NANOG as a transcription factor directly interacting with SRA and co-localizing with it genome-wide in NTERA2. Further, we show that SRA is important for maintaining the stem cell state and for reprogramming of human fibroblasts to achieve the pluripotent state. Our results suggest a mechanism whereby the lncRNA SRA interacts with either TrxG or PRC2. These complexes may then be recruited by various DNA binding factors to deliver either activating or silencing signals, or both, to establish bivalent domains.